Sacred Sites: Between Islamic and Hindu Traditions in Indonesia (A Comparative Study of Sacredness, Rituals, and Symbolism) - Kiriana, I Nyoman; Kholiq, Abdul; Dasih, I Gusti Ayu Ratna Pramesti; Widiasih, Ni Nyoman Sri (Journal of Posthumanism, 2025)
This study aims to compare the sacrality, rituals, and symbolism found in the Tomb of Sunan Kudus and the Tomb of Raja Udayana, two sacred sites representing Islamic and Hindu religious traditions in Indonesia. Through a qualitative approach, this research identifies the spiritual, cultural, and social values passed down by these tombs, as well as how the rituals and symbolism reflect each religion's understanding of the relationship between humans, nature, and God. The Tomb of Sunan Kudus, with its 'buka luwur' and 'ngalap berkah' traditions, highlights the influence of Islamic Sufism and the values of tolerance, while the Tomb of Raja Udayana, with its 'Pujawali' and 'Nyekah' rituals, embraces the 'Tri Hita Karana' teachings that harmonize humans, nature, and God. This study also emphasizes the role of these tombs as centers of pilgrimage and the preservation of tradition, as well as their influence in strengthening collective identity within the community. The findings indicate that, despite differences in teachings and ritual practices, both tombs share universal values regarding the importance of maintaining harmony, spirituality, and human relationships. These findings provide deeper insight into the role of sacred tombs in fostering interfaith tolerance and the preservation of cultural heritage in Indonesia.